Every bite counts to achieve oral health: a scoping review on diet and oral health preventive practices - Steffany Chamut; Mona Alhassan; Alhassan Hameedaldeen; Shivangi Kaplish; Adam H. Yang; Carrie G. Wade; Sondos Alghamdi; Denisse Chamut; Brian B. Novy; Tejasvita Chandel (International Journal for Equity in Health, 2024)
Abstract Objective To examine the landscape of preventive strategies and interventions directed to achieve oral health equity, with particular emphasis on the interplay between dental caries prevention, individual behaviors, and population-level strategies across various demographic and geographic regions. Methods This scoping review was guided by Peters et al.’s framework, which incorporates four key concepts aimed at reducing caries: education for individuals and healthcare providers, behavioral modifications, addressing broader social determinants of health, and extending oral health education programs beyond traditional dental settings. A systematic search was conducted across five databases, from 2011 to 2022. Results This review identified 107 studies highlighting three main themes: behavioral practices (N = 33), which focused on reducing the prevalence of caries, improving oral hygiene practices, and enhancing overall oral health knowledge; educational interventions (N = 39), which explored strategies to integrate oral health with broader public health initiatives; and dietary interventions (N = 35), which emphasized the critical relationship between diet and oral health. Conclusion This SR highlights the critical need for comprehensive multilevel approaches that address the complex interplay between nutrition, oral health, and sociodemographic factors, while emphasizing the critical relationship between societal factors and individual health behaviors. Multifaceted interventions that include behavioral change, education, and dietary modifications are crucial for improving oral and overall health outcomes across diverse populations. Comprehensive strategies should prioritize medical-dental integration and data-driven approaches to effectively reduce oral health disparities for vulnerable populations, promoting long-term health equity.